2022
DOI: 10.1007/s12035-022-03139-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Regulated Chaperones as a Serum Biomarker Panel for Parkinson’s Disease

Abstract: Examination of post-mortem brain tissues has previously revealed a strong association between Parkinson’s disease (PD) pathophysiology and endoplasmic reticulum (ER) stress. Evidence in the literature regarding the circulation of ER stress-regulated factors released from neurons provides a rationale for investigating ER stress biomarkers in the blood to aid diagnosis of PD. The levels of ER stress-regulated proteins in serum collected from 29 PD patients and 24 non-PD controls were measured using enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Increased levels of circulating MANF were detected in PD ( 54 ) and acute ischemic stroke ( 61 ), conditions related to the brain. When ER stress-regulated proteins in the blood were studied as potential biomarkers for PD, it was found that MANF together with three other proteins, PDIA1, PDIA3, and clusterin in combination with age and gender confounders were able to discriminate PD patients from the non-PD group ( 165 ). These studies suggest that the biomarker potential of MANF in PD should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of circulating MANF were detected in PD ( 54 ) and acute ischemic stroke ( 61 ), conditions related to the brain. When ER stress-regulated proteins in the blood were studied as potential biomarkers for PD, it was found that MANF together with three other proteins, PDIA1, PDIA3, and clusterin in combination with age and gender confounders were able to discriminate PD patients from the non-PD group ( 165 ). These studies suggest that the biomarker potential of MANF in PD should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is often a result of endoplasmic reticulum (ER) stress (47) that is also suggested to be involved in the pathophysiology of PD. Unlike molecular determinants of mitochondrial dysfunction, alterations of some critical molecular components of ER stress pathways were explicitly detected in brains of PD patients (48,49) previously and ER stress-regulated proteins were recently suggested as blood biomarkers to confirm the diagnosis of PD (50). Recent study has identified several proteins associated with mitochondrial functions that are significantly altered in brains of PD patients (46) but their use as biomarkers for PD will require additional experiments and validations.…”
Section: Mitochondrial Dna and Proteinsmentioning
confidence: 99%
“…Neuroinflammation and increased endoplasmic reticulum (ER) stress are implicated in the pathogenesis of PD making serum immune and ER stress marker profiles potential tools for the follow-up of the disease state [31,32]. However, their specificity to PD can be questioned as inflammatory cytokine levels and ER stress are elevated in a wide range of conditions [32]. Nevertheless, peripheral signs of inflammation should be considered for the biomarker battery of PD [31].…”
Section: Peripheral Body Fluidsmentioning
confidence: 99%
“…A meta-analysis by Rahmani et al [33] suggested reduced serum levels of brain-derived neurotrophic factor (BDNF) in PD patients as compared to healthy controls and showed that BDNF downregulation is associated with progressive motor symptoms. Thus, we should not forget NTFs as potential diagnostic biomarkers of PD [32,34].…”
Section: Peripheral Body Fluidsmentioning
confidence: 99%